High-frequency oscillations in human respiratory electromyograms during voluntary breathing - Bruce, E N; Goldman, M D (Brain research, 1983)
Electromyograms (EMGs) from respiratory muscles were obtained from human subjects during voluntarily controlled breathing. In 10 studies on 6 subjects EMGs were recorded from the right and left lower ventrolateral surface of the rib cage while the subject emphasized the use of his diaphragm for breathing. Simultaneous samples of the 2 EMG signals of 256-ms duration were obtained once per inspiration (in either the first of second half of inspiration) from each of 30 consecutive breaths using a laboratory minicomputer. Individual power spectra for the 2 EMG signals, and the squared coherence spectrum between them, were calculated. From the coherence spectrum common high-frequency oscillations could be identified within two frequency ranges: 70-100 Hz and 20-50 Hz. Peaks at similar frequencies were identified in both early-inspiratory and late-inspiratory EMG signals. Similar experiments were done on 3 subjects from whom an esophageal diaphragm EMG was obtained as well. The coherence spectrum between the esophageal EMG and the right rib cage surface EMG again demonstrated the presence of common high-frequency oscillations in the same frequency ranges as above. Evidence of these oscillations was not usually apparent in the power spectra. When ECG signal components were allowed to contaminate some of the EMG data samples, the coherence spectrum could be altered considerably, leading to inappropriate conclusions regarding the presence or absence of high-frequency oscillations. It is hypothesized that these high-frequency oscillations are similar to those described in nerve recordings from previous studies on anesthetized and decerebrate cats and dogs and a mechanism for their expression in EMG signals is proposed. The coherence spectrum is a very sensitive method for detecting related signal components in two signals. That high-frequency oscillations can be detected using the less sensitive techniques of autocorrelation and power spectral analysis in some animal preparations may reflect an enhancement of these oscillations in those preparations.